Application of Gamma Radiation on Hard Gelatin Capsules as Sterilization Technique and Its Consequences on the Chemical Structure of the Material - Rodrigues, James Teixeira; Souza Neto, Francisco Nunes de [UNESP]; Ferreira, Murillo Fernandes; Faleiro Naves, Plinio Lazaro; Guilherme, Luciana Rebelo (Springer, 2019)
Hard capsules are made from gelatin, an organic polymer obtained through the hydrolysis of collagen present in animal tissues. Gelatin can be degraded by microorganisms and some strategies can be used to control contaminating micro-organisms. Gamma irradiation is considered as an effective sterilization method; however, its application can alter the chemical structure of the irradiated product. Samples of hard gelatin capsules were irradiated at doses of 5, 15, and 25kGy at room temperature. The characterizations of the physical and chemical effects were evaluated by scanning electron microscopy, Fourier-transform infrared spectroscopy, X-ray diffractometry, and differential scanning calorimetry techniques. Furthermore, hard gelatin capsule samples were dissolved and inoculated with Bacillus subtilis, a Gram-positive spore-forming bacterium, to evaluate the effect of gamma ray radiation on bacterial counts. The results showed that gamma radiation did not interfere on physical parameters of the capsule, such as moisture content, mass, body and cap length, and disintegration time. Nevertheless, differential scanning calorimetry results demonstrated changes in the glass transition temperature, indicating the formation of crosslinking in irradiated capsules. It was observed that there were significant reductions on the inoculated bacterial population starting from the lowest irradiation dose and there was no detection of bacterial growth from the 15 kGy dose, while in the non-irradiated samples were found with 10(4)CFUmL(-1) of bacteria. Therefore, this work concludes that the gamma radiation is effective on the reduction of the microbial population, cause discrete physical-chemical alterations, and could be used as a hard capsule sterilization technique.
Keywords: sterilization; gelatin crystallinity; B; subtilis